PENILAIAN KESULITAN SOAL PTT BERDASARKAN HASIL BELAJAR SISWA PADA UPT SPF SD INPRES KARUWISI 2 - Sitti Rahma; Rukli; Erwin Akib (STKIP Subang, 2023)
This study aims to investigate the difficulty level of PTT (Midterm Assessment) questions according to students' perceptions and its impact on learning outcomes at UPT SPF (Formal Education Technical Implementation Unit) SD Inpres Karuwisi 2. The research sample consisted of 30 students in the fourth grade. Students' learning outcomes were assessed based on the interval grades, with the following findings: there was 1 student with a grade in interval 2.5, 1 student with a grade in interval 2, 10 students with grades in interval 2.5, 8 students with grades in interval 3, 7 students with grades in interval 3.5, and 3 students with grades in interval 4. The study concludes that the difficulty level of PTT questions significantly influences students' perceptions and learning outcomes. Questions that match students' ability level encourage motivation and interest in learning, while questions that are too difficult or too easy can negatively impact students' learning outcomes. Therefore, it is essential to adjust the difficulty level of PTT questions according to students' abilities to achieve optimal learning outcomes.